(untitled) (Prithvi Academic Journal, 2019)
What is the literary value of representing the culture of common people and making cultural discourse of marginality? For what purpose do the writers represent everyday lives, experiences, and cultural practices of marginalised groups? To answer these questions, this paper attempts to analyse Upendra Subba’s “Dumb Hill,” the title story of the anthology Dumb Hill, aiming to explore the whole way of life of ethnic Limbu people of Panchthar district, the eastern part of Nepal, including their lifestyles, socio-economic conditions, cultural values, and practices. It tries to interpret the purpose of representing everyday lives and cultural practices of common Limbu people. To interpret the text, Michel Foucault’s concept of discourse and power/knowledge, and Stuart Hall’s concept of representation have been applied as the theoretical tools to achieve the objectives of the study. Foucault argues that there is no truth, but truths which are constructed by power/knowledge and defined by the discourse. Discourse produces, constructs and defines a body of knowledge or truths. Hall undertakes the representation as a process and practice of conveying the meaning using the material objects or images, which are selected and constituted by power. In this sense, representation is a cultural product rather than an autonomous process of constructing a meaning. From this light, the story as a cultural discourse of marginality produces and defines overshadowed body of knowledge about ethnic Limbu people through discursive representation of Limbu people, and their distinctive cultural practices. This study provides a new insight to see and understand Limbu People’s distinctive ways of life that have been ignored and unheard in the dominant literary discourses.